Reconsidering palliative radiotherapy in addition to PD-1 blockade for non-small cell lung cancer: results from the FORCE phase II trial (AIO/YMO-TRK-0415) - Bozorgmehr, Farastuk; Chung, Inn; Fischer, Jürgen R.; Bischof, Marc; Atmaca, Akin; Wetzel, Sophie; Faehling, Martin; Bottke, Dirk; Wermke, Martin; Troost, Esther G. C.; Kropf-Sanchen, Cornelia; Wiegel, Thomas; et al. (Clinical & experimental metastasis, 2025)
Introduction of immune checkpoint inhibitors (ICI) has improved overall survival (OS) for advanced non-small cell lung cancer (NSCLC). However, responses differ greatly amongst patients. Additional radiotherapy (RT) may promote tumor-specific immunity and synergize with ICI to improve tumor control. The multicenter phase II FORCE trial evaluated safety and efficacy of nivolumab with additional palliative radiotherapy (5 × 4 Gy) as clinically indicated in pre-treated metastatic non-squamous NSCLC (group A, n = 41), including pretreated patients without an indication for radiotherapy in a parallel cohort as real-world controls (group B, n = 60). With an objective response rate (ORR) of 8.3% in group A (n = 41), the primary endpoint was not met (p = 0.991). ORR in group B (n = 60) was 23.8%. Patient characteristics indicated a significantly poorer baseline clinical condition for group A compared to B, including worse Eastern Cooperative Oncology Group (ECOG) performance status (PS, p = 0.020) and more metastatic sites (p = 0.009). Consequently, group A had shorter progression-free survival (median PFS, 1.9 versus 3.7 months, hazard ratio [HR] 1.69 [95% CI (1.10, 2.58)]) and OS (median 6.0 versus 12.6 months, HR 1.75 [95% CI (1.07, 2.84)]). In multivariable analyses for the intention-to-treat (ITT) population, ORR, PFS and OS were inversely associated with the patients’ ECOG PS (ORR odds ratio [OR] 0.126, p = 0.004) and correlated positively with tumor PD-L1 expression (ORR OR 12.8, p = 0.022), but not with radiotherapy administration (p = 0.169-0.854). Adverse events were distributed equally in both groups. Addition of palliative radiotherapy to nivolumab was safe and feasible, but not associated with improved efficacy. Patients with an indication for palliative radiotherapy have an inherently worse prognosis which cannot be overcome by radiation-induced immunostimulation. Clinical features and PD-L1 expression influence clinical outcomes more than radiotherapy administration and should be considered when evaluating the effectiveness of immuno-/radiotherapy combinations.
Gesehen am 18.12.2025